2017
DOI: 10.1155/2017/4521324
|View full text |Cite
|
Sign up to set email alerts
|

TNF-αInduced the Enhanced Apoptosis of Mesenchymal Stem Cells in Ankylosing Spondylitis by Overexpressing TRAIL-R2

Abstract: Ankylosing spondylitis (AS) is an autoimmune disease with unknown etiology. Dysregulated mesenchymal stem cells (MSCs) apoptosis may contribute to the pathogenesis of autoimmune diseases. However, apoptosis of MSCs from patients with AS (ASMSCs) has not been investigated yet. The present study aims to assess the apoptosis of bone marrow-derived ASMSCs and to investigate the underlying mechanisms of altered ASMSCs apoptosis. We successfully induced the apoptosis of ASMSCs and MSCs from healthy donors (HDMSCs) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…Thus, presence of HLA-DR molecules on some HD/ASC and RD/ASC lines, observed in our study ( Figure 1D), is unsurprising. Altogether, our results show that in terms of surface marker expression, RD/ASCs resemble ASCs obtained from healthy volunteers, which is consistent with other reports [36][37][38].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, presence of HLA-DR molecules on some HD/ASC and RD/ASC lines, observed in our study ( Figure 1D), is unsurprising. Altogether, our results show that in terms of surface marker expression, RD/ASCs resemble ASCs obtained from healthy volunteers, which is consistent with other reports [36][37][38].…”
Section: Discussionsupporting
confidence: 93%
“…A higher dose of TNF-α cause downregulation of MSCs type-2 signalling and induce apoptotic program through TNF-related apoptosis-inducing ligand-receptor 2 (TRAIL-R2) pathway. The similar study has reported that TNF-α may induce apoptotic through TRAIL-R2 pathway [ 24 ]. TRAIL-R2 is a specific cell surface receptor belongs to the TNF receptor superfamily [ 25 ] that also expressed in MSCs [ 26 ] [ 27 ].…”
Section: Discussionmentioning
confidence: 86%
“…Similar effects have been observed on MSCs derived from patients with autoimmune diseases. For instance, it has been shown that TNF treatment decreased the HGF production by BM-MSCs derived from SLE patients via the TNFR1/IKK-β pathway ( 80 ) and induced apoptosis in BM-MSCs from ankylosing spondylitis patients via TNFR1-mediated upregulation of TRAIL-R2 ( 133 ).…”
Section: Tnf Regulation Of Msc Efficacy On Autoimmune and Inflammatormentioning
confidence: 99%